College Students' Perceptions of an Automated Writing Evaluation as a Supplementary Feedback Tool in a Writing Class - Ariyanto, Meilisa Sindy Astika; Mukminatien, Nur; Tresnadewi, Sintha (Universitas Negeri Malang, 2021)
Automated Writing Evaluation (AWE) programs have emerged as the latest trend in EFL writing classes. AWE programs act as a supplementary to teacher feedback and offer automated suggestions and corrections to students' linguistic errors such as grammar, vocabulary, or mechanics. As there is a need for better recognition of different AWE brands utilized for different levels of students, this research sheds light on identifying six university students’ views of an AWE program, namely ProWritingAid (PWA). The six students are categorized as having high or low writing achievement. This descriptive study delineates the students’ perceptions qualitatively. A semi-structured interview was used to collect the data. The findings suggest the students’ positive views of PWA because it could make class time more effective; it had useful feedback on grammar, vocabulary choices, and mechanics; and it built students‘ self-confidence over their compositions. In addition, for different reasons, the students engaged differently with PWA to enhance their drafts, e.g. using PWA only for the first drafts or for the first and final drafts. Finally, despite of the students’ constructive views on PWA, there was a risk that students only engaged superficially with the program by hitting the correction directly.